2013
DOI: 10.1007/s00170-013-5037-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cutting conditions of YG15 on rough and finish cutting in WEDM based on statistical analyses

Abstract: In this paper, the effects and the optimization of cutting parameters on surface roughness (Ra) and material removal rate (MRR) in the wire electrical discharge machining (WEDM) of high hardness tool steel YG15 are analyzed. In the WEDM process, the key process parameters, such as pulse-on time, pulse-off time, power, cutting feed rate, wire tension, wire speed, and water pressure, are optimized. Experimental data were initially collected based on the Taguchi method of experimental design, which are L 18 2 1 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 19 publications
3
11
0
1
Order By: Relevance
“…In statistical analyses, the factor effect is defined as the difference between the two extreme values of the response obtained for the corresponding factor, and the relatively factor effect is defined as Eq. 17, where RE i is the i th relatively factor effect, and E i is the i th factor effect [44,45]. The graphical assessment also can be depicted from Fig.…”
Section: Main Effect Analysis For Mrr and Ramentioning
confidence: 94%
“…In statistical analyses, the factor effect is defined as the difference between the two extreme values of the response obtained for the corresponding factor, and the relatively factor effect is defined as Eq. 17, where RE i is the i th relatively factor effect, and E i is the i th factor effect [44,45]. The graphical assessment also can be depicted from Fig.…”
Section: Main Effect Analysis For Mrr and Ramentioning
confidence: 94%
“…The minimum and maximum value of infeed were determined based on the previous research of the authors. The initial range of the infeed values calculated according to [ 49 ] was adapted in tests to find the minimum value allowing for the electric discharge between the wire electrode and the workpiece, and the maximum value allowing for the machining without short circuits or breaking the wire. Thus, the infeed range for finishing machining was z = 30–70 μm.…”
Section: Methodsmentioning
confidence: 99%
“…e ANOVA is carried out for the obtained GFRG which shows the impact of various process parameters from Table 10; it had been observed that the obtained ANOVA table does not give su cient results since the degrees of freedom (DOF) for the error term is zero. is happens due to the mismatching of the input parameters and the level of each parameter.…”
Section: Resultsmentioning
confidence: 99%
“…e experiments have been conducted by changing pulse on time, pulse off time, and peak current. Huang et al [10] observed the influence of various process parameters on surface quality, material removal rate, and average gap voltage in the WEDM of high hardness tool steel YG15. Regression models are used to obtain the optimum cutting parameter combination.…”
Section: Introductionmentioning
confidence: 99%